2017
DOI: 10.1590/s1980-6574201700si0062
|View full text |Cite
|
Sign up to set email alerts
|

Parental education and perception of outdoor playing time for preschoolers

Abstract: -Aim:The objective of this study was to analyze whether or not socioeconomic positions influence outdoor playtime during the week (WK) and on the weekends (WEND). Methods: The sample consisted of 485 (girls; n=223) healthy preschoolers, aged from 3 to 6 years, enrolled in kindergartens from the metropolitan area of Porto, Portugal.Physical Activity (PA) was assessed for 7 consecutive days with an accelerometer. The time playing outdoors during the WK or the WEND was reported by parents. Anthropometric data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
6
2
Order By: Relevance
“…One of the few Portuguese studies on AOP showed that socioeconomic position can influence children's time spent in outdoor activities, especially on the weekends. 28 However, our data found no significant differences for parental education, as a proxy for socioeconomic status (SES).…”
Section: Discussioncontrasting
confidence: 68%
“…One of the few Portuguese studies on AOP showed that socioeconomic position can influence children's time spent in outdoor activities, especially on the weekends. 28 However, our data found no significant differences for parental education, as a proxy for socioeconomic status (SES).…”
Section: Discussioncontrasting
confidence: 68%
“…Confusion in terminology of outdoor play/time is well-noted in previous literature [20,151]. In our review, outdoor physical activity [35,39,47,63,65,67,77,86,103,113,119,152], outdoor activity, outdoor playtime [38,68,100,137], playground usage [30,108], active free play [122], outdoor active play [61] and in different settings (e.g., playground, on street, during recess) were observed in addition to outdoor play/time. Establishing clear definitions of outdoor play, outdoor time, and other relevant terms may not only reduce the confusion that exist in the field but may also advance the measurement of outdoor play and outdoor time.…”
Section: Discussionmentioning
confidence: 60%
“…In four studies school grade was reported (1st grade, n = 1; 5th grade, n = 2, prekindergarten to 6th grade, n = 1) [47,59,102,113,132]. The quality rating scores are presented in Supplementary Table 3 [39,51,57,62,70,71,74,83,99,100,103,107,108,114,130], of which one observation used both proxy-and selfreported data [102]. Ten studies used accelerometry or pedometry (i.e., device-based measures of physical activity that took place outdoors) [34,35,48,72,77,86…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Playing provides an opportunity for children to adapt to others and the environment and impacts on their motor development, thinking ability, and the ability to solve problems [1]. There are still many parents who prioritize children's academic skills in reading and mathematics, because they assume that being good at reading and math means having more abilities [2]. This kind of assumption is based on the presumption that play is a waste of time.…”
Section: Introductionmentioning
confidence: 99%